PSXI-24 Rumen temperature, fermentation and microbial signatures are poorly associated with steer feed-efficiency profiles. (5th December 2019) - Durunna, Obioha N; Damiran, Daalkhaijav; Campbell, John R; Carroll, Jeffery A; Lardner, Bart
Abstract: Breeding feed-efficient cattle can reduce the environmental footprint of beef operations but assessing all replacement candidates for feed-intake is not practical due to cost implications. The main objectives of this study were to evaluate if rumen temperature (RumT), measured with wireless rumen Thermobolus® can distinguish steers with different feed-efficiency profiles and whether steers with divergent efficiency profiles have different nutrient fermentation signatures. The study also validated the relationship between rectal temperature (RecT) and RumT measured with automatic thermistors. Residual feed intake (RFI) profiles of 160 steers were measured over two years. All steers were assessed for RFI profiles using high and moderate forage diets, respectively, over two successive periods each year. Each steer was fitted with a rumen Thermobolus® throughout each 80-d test period while half of the steers wore an automatic temperature-logger rectal device for 30d. The devices recorded the RumT and RecT every 5 minutes, respectively. Rumen fluid samples were collected from high-RFI (n = 5) and low-RFI (n = 5) steers to assess if differences in rumen fermentation and microbial profiles exist. Circadian-adjusted RumT and RecT for each steer were used for analysis. The within-period correlations between RumT and RecT ranged between 49 and 77%. There was a trend (P = 0.08) that differences exist for rhythm-adjusted temperatures among different RFI profiles with low-RFI steers (39.72±0.01 o C) having lower average RumT than those in high (39.75±0.01 o C) or medium (39.74±0.01 o C) classes. The correlation between the two test-periods for rhythm-adjusted RumT was 65% while the correlation between RFI from both periods was 47%. There was no difference (P > 0.30) between high- and low-RFI animals for the total or individual volatile fatty acid fractions or microbial populations. The narrow temperature variation among RFI classes limits its use as screening tool but the higher across-period correlation encourages the need for further studies into alternative potential applications.